Reduced Cortical Inhibition and EEG Response to Transcranial Magnetic Stimulation in ADHD - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2012)
Investigators at University of Heidelberg and other centers in Germany employed the N100 component of the EEG response to transcranial magnetic stimulation (TMS) as a novel marker for direct assessment of cortical inhibition in children with ADHD.